Pathophysiological Models of Hypersomnolence Associated With Depression - Christophe Moderie; Diane B. Boivin (Biological Psychiatry Global Open Science)
Up to 25% of patients with depression experience hypersomnolence (e.g., excessive daytime sleepiness, hypersomnia, and/or sleep inertia), which is associated with treatment resistance, overall poorer outcomes, and safety concerns while driving. Hypersomnolence can result from various sleep/neurological disorders or side effects from medication but is often medically unexplained in depression. In this review, we aimed to summarize the different pathophysiological models of hypersomnolence in depression to discuss their impact on nosology and to foster the development of better tailored diagnostics and treatments. We identified several potential mechanisms underlying hypersomnolence including a daytime hypoactivity of dopaminergic and noradrenergic systems, nighttime GABA (gamma-aminobutyric acid) hypoactivation, hypoperfusion, and hypoconnectivity in the medial prefrontal cortex, as well as a longer circadian period and light hyposensitivity. In some patients with depression, nighttime hyperarousal can fragment sleep and result in a complaint of excessive daytime sleepiness, thus mimicking hypersomnolence. Others might adopt maladaptive behaviors such as spending excessive time in bed, a term coined clinophilia. Objective markers of hypersomnolence, such as ambulatory ad libitum polysomnography may facilitate distinguishing between conditions that mimic hypersomnolence. Our review identified several clinical targets for hypersomnolence in depression. Low-sodium oxybate, which is approved for idiopathic hypersomnia, needs additional study in patients with depression. Neuromodulation that targets prefrontal cortex anomalies should be systematically explored, while tailored light therapy protocols may mitigate light hyposensitivity. Additionally, cognitive behavioral therapy for hypersomnolence is being developed as a nonpharmacological adjunct to these treatments.